1996
DOI: 10.1051/jp4:19968175
|View full text |Cite
|
Sign up to set email alerts
|

Domain Freezing in Triglycine Sulphate

Abstract: Domain freezing is observed for the first time in triglycine sulphate. A new domain freezing model is proposed based upon the collective-pinning of random distributing pinning centers to DW's, and Vogel-Fulcher relation, which describes the relaxation during the process of domain freezing successfully, is deduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The R 2 peak is commonly attributed to domain walls. Its behavior is close to that observed by Wang et al [6,15] in the case of ferroelectric La 1x Nd x P 5 O 14 . This peak does not follow the Arrhenius equation and the model of viscous motion of domain walls in the lattice can be applied.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The R 2 peak is commonly attributed to domain walls. Its behavior is close to that observed by Wang et al [6,15] in the case of ferroelectric La 1x Nd x P 5 O 14 . This peak does not follow the Arrhenius equation and the model of viscous motion of domain walls in the lattice can be applied.…”
supporting
confidence: 90%
“…At low temperature, a collective pinning of domain walls can occur leading to a freezing of domain walls near a temperature T f [6]. When the temperature is increased, collective pinning becomes weaker due to thermal fluctuation and individual pinning occurs.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the susceptibility drops down to the domainaveraged value. Such behaviour was found for example in dielectric measurements of KH 2 PO 4 (KDP) 14 and (NH 2 CH 2 COOH) 3 • H 2 SO 4 (TGS) 15 and in elastic measurements of KMnF 3 9,16 , PbZrO 3 13 and LaAlO 3 11 .…”
Section: Introductionmentioning
confidence: 59%
“…Let us look at the various terms in Eq. (9). Electron Microscopy studies 48 revealed a small domain wall thickness of the order of unit cell dimensions.…”
Section: Discussionmentioning
confidence: 96%